Wet‐Snow Metamorphism Drives the Transition From Preferential to Matrix Flow in Snow. Issue 24 (27th December 2019) - Hirashima, Hiroyuki; Avanzi, Francesco; Wever, Nander
Abstract: In order to explain the poorly understood transition between preferential and matrix flow in snow, we compared observations from a cold‐laboratory experiment with predictions from a multidimensional water transport snow model. We found a good agreement between the modeled and observed evolution of grain size distributions if two or three dimensions are considered by the model, which validates existing theories of snow grain growth. Furthermore, the model reproduced the spatial migration of preferential flow paths with time and a progressive homogenization of snow wetness and structure only if grain growth was simulated. Spatially varying grain growth thus drives the transition from a preferential flow to a matrix flow regime. This transition is faster when grain size and density are lower, or infiltration rates are higher. This explains why preferential flow is more persistent in firn than in snow. Key Points: Model predictions of grain growth in wet snow agree with laboratory observations Spatially varying grain growth rates drive the migration of preferential flow paths with time This migration explains the transition from preferential to matrix flow in snow